PROGRAM PEMBERDAYAAN MOTIVATIONAL INTERVIEWING UNTUK MENINGKATKAN MANAJEMEN DIRI DAN KONTROL GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 DI DESA LAMAHU PROVINSI GORONTALO - Ratnawati Ratnawati; Fakhriatul Falah; Paulus Pangalo (Jurnal Abdimas Bina Bangsa, 2023)
Diabetes Mellitus (DM) is a chronic condition that occurs when there is an increase in glucose levels in the blood because the body cannot produce enough insulin hormones effectively. Gorontalo Province is also an area where the prevalence of type 2 DM sufferers is quite high. This is caused by insufficient self-management and insufficient self-awareness to improve health. Improving the self-management of type 2 diabetes patients can be improved through a motivational interviewing program. The aim of this community service activity is to empower community cadres and social groups through a motivational interviewing program for people with type 2 diabetes mellitus. The activity is carried out in two stages, in the first stage providing outreach in the form of lectures and discussions about type 2 diabetes mellitus and motivational program training interviewing. After that, cadres and community social groups provide assistance to type 2 diabetes mellitus patients for one week. Then in the second stage, the results of the mentoring are evaluated. The evaluation results showed that there was a decrease in blood sugar of 53.57 mg/dL. From the results of this activity, it can be concluded that the motivational interviewing program is recommended for self-management of type 2 Diabetes Mellitus patients